Manfaat Yoga Bagi Kesehatan Mental Pada Remaja - Novitasari, Ayuningtyas (Jayapangus Press, 2022)
Yoga is a practice that can help to achieve calmness and emotional balance, as well as better focus and concentration. Yoga in its original sense was designed as a method of spiritual awakening but has recently been accepted as a health science. Yoga is currently used as a hea lth care method. Yoga can not only prevent and cure diseases, but it can also help maintain good health. Yoga focuses on strengthening the defense system of the body and mind, rather than on eliminating disease-causing factors. Yoga can improve immunity, help the body and mind achieve balance, and prevent the onset of disease. Therefore, yoga aims to achieve physical, mental, social, and spiritual health. This study uses a qualitative research method approach. The results of this study are Yoga not only moves the physical body, but also stimulates various glands, muscles, and body parts related to emotional activity or state of mind. The nervous system can be activated or calmed through Asana, breath control or Pranayama, and meditation. Yoga is a state of strong steadfastness on the emotional level, yoga creates a state of strong inner steadfastness on the emotional level, balance concentration, and an independent attitudeon the mental level, balanced concentration, and an indepedent attitude on the mental level, while maintaining homeostatic balance on the physical level. In this context, yoga reflects a state of integration of personality, harmony between body and mind. Achived in a state of optimal balance. Meditation and pranayama are integral element in the concept of yoga as explained in the teaching af astanga yoga. Succes in practicing yoga can bring practitioners out of the infuence of the five klesas, which include the five factors that cause suffering such as avidya, asmita, raga, dvesa and abhinivesa. Factors that influence mental health are stress, tension, fear, depresion, insomnia, anxiety, phobias, despair. Other mental health conditions that affect teenagers include bipolar disorder, behavioral disorders, attention deficit hyperactrivity disorder, learning disoders, eating disorders, autism and chilhood onset schizophrenia. Seeing that teenagers are facing a lot of problems in today's era which may be due to the hectic schedule from morning to evening to bedtime, they do not have time for themselves. With the help of doing Yoga, they can easily achieve good mental and physical health.